Comparative Study of Efficacy of Hemidesmus Indicus (L.) R. Br. and Decalepis Hamiltonii Wight & Arn. in Acne Vulgaris (Mukhadushika) - Parul Nandgaonkar1 , Pramod Khobragade2 , Vaishali Kuchewar3 , Akshay Pargaonkar4 , Pradeep Nandgaon (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hemidesmus indicus (L.) R. Br. (Sariva) commonly known as Anantmool with its unique attributes is used intherapeutics in Ayurveda. From few decades due to heavy demand and extreme commercial collection fromnatural habitat of this plant its natural population is decreasing with higher rate and has resulted in extinctionof population. In various Ayurvedic raw drug market and in the leading Ayurvedic pharmacies, the roots ofDecalepis hamiltonii which is considered as Sariva species is used in place of the roots of H. indicus (Sariva)in Ayurvedic formulations. H. indicus though is cultivated by special method, still it is very time consumingand expensive process. D. hamiltonii is easily cultivated with high yield and less expensive as compared toH. indicus. The present study was undertaken to compare the efficacy of Hemidesmus indicus (L.) R. Br. andDecalepis hamiltonii Wight & Arn. In Acne vulgaris (Mukhadushika)and compare its efficacy. On the basisof the observation obtained both drugs relieved symptoms burning sensation (Daha), pain (Vedana), itching(Kandu),erythema(Lalima) and Global acne grading scale (GAGS) of Acne vulgaris significantly. As perstudy it is concluded that tablet (Ghana Vati) and Gel of Hemidesmus indicus and Decalepis hamiltonii areequally effective in the management of Acne vulgaris. Hence D. hamiltonii can be used as substitute drug ofHemidesmus indicus in the management of Acne vulgaris.